Physical and Chemical Treatments on Chitosan Matrix to Modify Film Properties and Kinetics of Biodegradation - Rivero, Sandra (2013)
This work was focused on analyzing the effect produced by the addition of tannic acid as a crosslinking agent of chitosan matrix and the influence of the heat treatment applied. Taking into account those aspects relevant for packaging applications, thermal stability, mechanical properties, water resistance and kinetics of biodegradation of the film were monitored. The chemical crosslinking as well as the curing of the matrices have improved the mechanical properties and those related to the water affinity such as solubility, permeability and contact angle. Although both processes had an influence on the extent of the film degradation, these materials conserved their biodegradable character. Moreover, it was observed a synergistic effect of both chemical and physical treatments since the two processes in simultaneous caused further delay in the biodegradation. Consequently, in these materials the access to fungal attack and all those reactions mediated by the presence of water were restricted, which confirmed the higher stability of the matrices submitted to chemical or physical crosslinking.